Animal bite injuries in pediatric population: a systematic review - Singhal Ruchi; Sikka Neha; Namdev Ritu (EDP Sciences, 2022)
Objectives: To assess the scientific literature pertaining the risk factors for injuries among victims of animal bite injuries. Data and sources: A systematic review of scientific literature published until May 2020 was carried out in the following databases: PubMed, Cochrane Library, Google Scholar and Journals@ovid. Study selection: A total of 924 records were found, of which 29 articles fulfilled the inclusion criteria and were analyzed. There was a male preponderance in most of the studies with male/female ratio ranging from 0.75:1 to 2.1:1. The age range varies from 0 to 19 years with the mean age varying from 3.6 to 8 years. Pitbulls, Rottweiler's, German shepherds, Bull terriers, Labradors and Dobermans were breeds with higher risk of attack. The animals were familiar to the victim (own, friends, neighbors) in 27-98% instances. Most cases of animal bite injuries were recorded during Summer and Spring months. Head and neck followed by extremities was found to be most inflicted area. Conclusions: The sociodemographic characteristics of victim as well as the biting animal affect the circumstances leading to biting episode. However, the results should be interpreted with caution due to the high heterogeneity among studies and moderate quality evidence.